Coronavirus as an (Anti)Hero of Fairy Tales and Guides for Children - Jolanta Karbowniczek; Beata Kucharska (Ignatianum University Press, 2020)
Nowadays, preschool and school children develop, are raised, and learn in a new reality for them, caused by the coronavirus pandemic. Including the assumptions of the connectivist paradigm as a novelty in the didactic activities of teachers, remote e-learning, computer games, board games, e-books, audiobooks, and multimedia programs fill free time and are becoming a way of learning and teaching in the digital age. The literary genre introducing children to the world of the contemporary threat of COVID 19 is the new fairy tale and therapeutic children's story, thanks to which events and characters struggling with the prevailing pandemic around the world are presented. The purpose of the article is to analyze and interpret innovative proposals for e-books of fairy tales which explain to young children what the coronavirus pandemic is, how to guard against it, what is happening in Poland and around the world, how to behave, and what actions to take to prevent the spread of viruses. In their discussion, the authors emphasize the psychological, sociological, and therapeutic aspects of the presented content of fairy tales, which are most often related to experiences, emotional sensitivity, anxiety, a fear of something bad, an identification with the characters, and overcoming any difficulties in this situation which is trying for all.